Effect of Using Web-Blog on Writing Instruction for English Language Learners - Arochman, Taufik; Yosintha, Rolisda (JOLLT Journal of Languages and Language Teaching, 2020)
This study was aimed to find out the effectiveness of an intervention using a Web blog to enhance the academic writing of English Language Learners. It tries to reveal whether there is any effect in the writing ability of the students taught using Web blog (online) and that of those taught without using it (offline). This study was classified as quasi-experimental research. The sample of this research was 64 students of X Unggulan Classes (XU1 and XU2) at the secondary school level in central java. Class XU2 was chosen as the Experimental Group taught using Web blog media as the treatment employed, whereas Class XU1 as the Control Group, which was not given the treatment (employed other media). Between the beginning and the end of the study, they were given three months of treatment. The results showed that there was an important effect in the writing ability of the students taught using Web blog and that of those taught without using it. It can be seen in the result of the hypothesis testing that the t-observed (2.028) is higher than the t-table (1.671).